Diseño de un plan estratégico de marketing para la exportación y comercialización de un insecticida de uso doméstico a mercados latinoamericanos y de EEUU (2017)
The Larssen laboratory like many companies in Colombia want to maintain and grow in the changing and more demanding market of today, improving their competitiveness and for them it is considered that the factors of international marketing within the most important factors that can help this objective . The elements that make up international marketing manage to adapt the product to the demands of the market and the possibilities of the company, and offer the competitive elements demanded by the international client.